POPULATION STRUCTURES OF FOUR TREE SPECIES IN LOGGPOPULATION STRUCTURES OF FOUR TREE SPECIES IN LOGGED-OVER TROPICAL FOREST IN SOUTH PAPUA, INDONESIA: AN INTEGRAL PROJECTION MODEL APPROACH - Kuswandi, Relawan; Murdjoko, Agustinus (Secretariat of Forestry Research and Development Agency, 2015)
Selective logging has been taking place in Papua for several decades. In contrast, very little is known about the stand structure in post-logged forest. Hence, this paper investigates stand structures in logged-over area of tropical forest in South Papua. Four species were selected in three one-hectare permanent sample plots (PSPs): Vatica rassak, Syzygium sp, Litsea timoriana and Canarium asperum. PSPs were located in the forest concession area of PT. Tunas Sawaerma in Assiki, Boven Digul, in South Papua. Data sets comprised measurements made in 2005 and 2012 consisting of species, diameter at breast height (DBH), mortality and number of tree of each species. Integral Projection Models (IPMs) were developed, taking into account mortality, growth, recruitment and fecundity. Results show the pattern of stand structures of the four species were more or less similar, i.e. more individual trees were present in the small diameter classes than in the larger diameter classes. The general pattern of the individual distribution of the four species is the typical reverse-J shape. Syzygium sp. has a greater number of individuals in the small diameter classes than the other three species. Population growth rates (λ) are above one, indicating that the stand structures of the population dynamics of the four species are recuperating. Conclusively, these results suggest that species composition and population structure in these logged-over forests are recovering increasingly.